THE RELATIONSHIP BETWEEN GOOGLE SEARCH VOLUME AND FLOOD EVENTS IN INDONESIA: A GOOGLE TRENDS ANALYSIS - RESTI KINANTHI; Mochammad Iqbal (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The increasing number of floods every year brings a wide impact; the average loss caused by floods every year reaches 4.64T (Rp). Information about floods is very important to improve the preparedness of people living in disaster-prone areas. If information can be provided when people have a high interest in learning, it can have a profound effect on increasing public knowledge. To carry out effective risk communication in flood disasters, knowledge about flood disaster patterns is needed, as well as knowledge about community behavior in seeking information. One of the people's behavior in searching for information can be seen from the Google Trends analysis. The purposes of this study are to analyse the relationship between public interest in finding information through google trends with the keyword "flood" with flood events in Indonesia for 10 years. This research is a quantitative descriptive study by processing data obtained from Google Trends and BNPB flood event data using the Spearman Rank Correlation statistical test with SPSS software. The results showed that Google Trends with the keyword "Flood" and the pattern of flood events had a strong positive relationship with a correlation coefficient of 0.64, this indicates that the increase in the incidence of disasters causes an increase in public interest in seeking information about flood disasters. Risk communication that was carried out before the disaster occurred was not yet optimal in reaching the community. Risk communication needs to be carried out before the months that are predicted to be the peak of flood events. Risk communication is carried out to form the preparedness of the Indonesian people so that the risk of flood disasters can be reduced.